Activation of p53 in cervical carcinoma cells by small molecules - Hietanen, Sakari (The National Academy of Sciences, 2000)
In over 90% of cervical cancers and cancer-derived cell lines, the p53 tumor suppressor pathway is disrupted by human papillomavirus (HPV). The HPV E6 protein promotes the degradation of p53 and thus inhibits the stabilization and activation of p53 that would normally occur in response to HPV E7 oncogene expression. Restoration of p53 function in these cells by blocking this pathway should promote a selective therapeutic affect. Here we show that treatment with the small molecule nuclear export inhibitor, leptomycin B, and actinomycin D leads to the accumulation of transcriptionally active p53 in the nucleus of HeLa, CaSki, and SiHa cells. Northern blot analyses showed that both actinomycin D and leptomycin B reduced the amount of HPV E6-E7 mRNA whereas combined treatment with the drugs showed almost complete disappearance of the viral mRNA. The combined treatment activated p53-dependant transcription, and increases in both p21(WAF1/CIP1) and Hdm2 mRNA were seen. The combined treatment resulted in apoptotic death in the cells, as evidenced by nuclear fragmentation and PARP-cleavage indicative of caspase 3 activity. These effects were greatly reduced by expressing a dominant negative p53 protein. The present study shows that small molecules can reactivate p53 in cervical carcinoma cells, and this reactivation is associated with an extensive biological response, including the induction of the apoptotic death of the cells.